2020
DOI: 10.1002/app.49588
|View full text |Cite
|
Sign up to set email alerts
|

Melt spinnability of long chain cellulose esters

Abstract: Technical and hygienic nonwovens, originating typically from fossil‐based synthetic polymers, are the fastest growing applications in the textile industry. Recently developed thermoplastic cellulose fatty acid esters have polyolefin like rheology properties and therefore the suitability of these cellulose esters for fiber production was evaluated. In this study, the melt spinning of textile fibers has been demonstrated using thermoplastic cellulose octanoate. The mechanical properties of melt spun fibers were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Therefore, the sequence of activities to produce this material includes the optimization of the electrospinning process and, simultaneously, the process of incorporating essential oils, via coaxial electrospinning (core/shell needle) and dual‐jet electrospinning (adjacent needles). Another form of fiber production is meltspinning, in which PET is melted at 130°C; 23 however, this technique would decompose or volatilize the essential oil. Therefore, the wet spinning technique is more viable.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the sequence of activities to produce this material includes the optimization of the electrospinning process and, simultaneously, the process of incorporating essential oils, via coaxial electrospinning (core/shell needle) and dual‐jet electrospinning (adjacent needles). Another form of fiber production is meltspinning, in which PET is melted at 130°C; 23 however, this technique would decompose or volatilize the essential oil. Therefore, the wet spinning technique is more viable.…”
Section: Resultsmentioning
confidence: 99%
“…[203] For example, cellulose octanoate (C8) and cellulose palmitate (C16) are thermally processible without using plasticizers. [204] However, chemical modification with long chain fatty acids usually requires high temperature, long reaction times, catalysts, and/or special acylation to enhance reactivity. [205] These harsh conditions often cause significant degradation of the cellulose and makes the process expensive and less efficient.…”
Section: Cellulose Thermal Processingmentioning
confidence: 99%
“…The spun-laid technique uses polymers hard to break down while the air-laid and wet-laid forming processes utilize short fibers to form webs and bonds them with binders that are biodegradable or water-soluble (Blackburn 2005;Russel 2007). However, nowadays, there is a lot of work seeking the inclusion of bio-based materials in the spun-laid technology, as the recent work by Willberg-Keyrila ¨inen et al (Willberg-Keyrila ¨inen et al 2020) which shows the use of thermoplastic cellulose fatty acid esters with a polyolefin-like rheology properties for fiber production. The authors concluded that these novel cellulose-based fibers can provide a renewable and recyclable alternative for spun-laid PP in several hygienic textile.…”
Section: Introductionmentioning
confidence: 99%